A152 TREATMENT SEQUENCE NETWORK-META ANALYSIS IN CROHN'S DISEASE. (1st March 2018) - Varu, A; Palimaka, S; Hutton, B; Wilson, F R; Dyrda, P; Naessens, D; Cameron, C
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory condition of the intestinal tract. There are various treatments available for CD, including a recently developed treatment – ustekinumab (Stelara®). Aims: The objective of this network meta-analysis (NMA) was to assess the comparative efficacy of ustekinumab and vedolizumab in the maintenance of clinical response and remission, after 1 year of treatment. Methods: A systematic literature search was performed to identify RCTs published in English comparing biologic therapies for patients with moderate-to-severe CD. Key outcomes of interest were clinical response (CD activity index [CDAI] reduction of 100 points; CDAI-100) and remission (CDAI<150), during maintenance treatment. A Treatment Sequence Bayesian NMA was conducted in order to account for re-randomization after induction of patients based on different clinical definitions (CDAI-70/100 response), the lack of similarity of the common comparator (placebo) in maintenance due to different induction treatment, and the full treatment pathway from induction. Results: A total of thirteen RCTs were identified. Overall, ustekinumab 90 mg q8w was associated with statistically significant maintenance of clinical response (OR [95% CrI]: 1.66 [1.05; 2.62]) and clinical remission (OR 1.74 [1.05; 2.88]) relative to vedolizumab 300 mg q8w. Additionally, ustekinumab 90 mg q12w was associated with statistically significant maintenance of clinical response (OR [95% CrI]: 1.60 [1.01; 2.54]) relative to vedolizumab 300mg q8w. Findings for failed conventional and failed anti-tumor necrosis factor sub-populations are similar to those in the overall population but were not statistically significant, likely due to small sample sizes. Conclusions: The results of the current NMA suggest that ustekinumab is associated with the highest likelihood of maintaining response or remission at 1 year compared with vedolizumab. Results should be interpreted with caution due to methodological limitations; however, the treatment sequence analysis may be the most methodologically sound analysis to derive estimates of comparative efficacy in CD in the absence of head-to-head evidence. Funding Agencies: Janssen Inc.